The Miocene fossil lizards from Kutch (Gujarat), India: a rare window to the past diversity of this subcontinent. (January 2022) - Čerňanský, Andrej; Singh, Ningthoujam Premjit; Patnaik, Rajeev; Sharma, K. Milankumar; Tiwari, Raghavendra Prasad; Sehgal, Ramesh Kumar; Singh, Nongmaithem Amardas; Choudhary, Deepak
Abstract: The Miocene beds of Kutch in India are well known for their mammalian assemblages, including the extinct ape Sivapithecus, but far less is known about the fossil squamates from this area. Although India with its over 800 reptile species is recognized as one of the global biodiversity hotspots, knowledge of past diversity and paleobiogeography of squamates on this subcontinent is very limited. We here report on new lizard finds, which have been recovered from two stratigraphic levels: the older Palasava locality (dated to the middle Miocene, ca. 14 Ma) and the younger Tapar site (late Miocene, ca. 11–10 Ma). Although fragmentarily preserved, the material described here sheds important light on the composition and paleobiogeography of squamates during the Miocene in South Asia. The older Palasava locality contains cf. Uromastyx s.l. and Varanus sp., the latter representing the oldest record of this taxon in the region of India south of the Himalayas and its occurrence here suggests a mean annual temperature not less than 15°C. The material from the younger Tapar locality consists of an unidentified acrodontan lizard, here questionably placed in agamids, and a skink. The latter shows a resemblance to mabuyines, however, the fragmentary nature of the material does not allow a precise allocation without doubts. The cosmopolitan mabuyines have been suggested to have their origin in Asia, so the potential presence of mabuyines in the Tapar locality might represent the first, but putative, Asian evidence of the occurrence of this group in the Miocene.